2020
DOI: 10.1161/jaha.119.015302
|View full text |Cite|
|
Sign up to set email alerts
|

Access to Cardiovascular Disease and Hypertension Medicines in Developing Countries: An Analysis of Essential Medicine Lists, Price, Availability, and Affordability

Abstract: Background Access to medicines is important for long‐term care of cardiovascular diseases and hypertension. This study provides a cross‐country assessment of availability, prices, and affordability of cardiovascular disease and hypertension medicines to identify areas for improvement in access to medication treatment. Methods and Results We used the World Health Organization online repository of national essential medicines lists ( EML s) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 21 publications
2
74
0
1
Order By: Relevance
“…These regional and national differences in total CVD burden and mortality reflect differences in prevalence of CVD risk factors as well as access to health care ( 8 ). Differences in access to effective primary and secondary prevention strategies may also play a role in differences in total CVD burden, especially in low- and middle-income countries (LMICs) ( 9 ).…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…These regional and national differences in total CVD burden and mortality reflect differences in prevalence of CVD risk factors as well as access to health care ( 8 ). Differences in access to effective primary and secondary prevention strategies may also play a role in differences in total CVD burden, especially in low- and middle-income countries (LMICs) ( 9 ).…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…These results imply that the richer areas of the world are more likely to have lower CVD burden than those in poorer territories. It seems this regional diversity in the CVD burden reflects the differences in the awareness about this disease, controlling the potential risk factors, screening programs, availability of proper treatment, as well as the level of patients’ care in different populations [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“… 19 In a recent study conducted by Husain et al based on the WHO online repository of national essential medicines lists for 53 countries, the average availability of the essential CVD medications was 54% in LICs and lower-middle-income countries (LMICs) and 60% in HICs and upper-middle-income countries (UMICs). 20 They also found that affordability was lower in LICs and LMICs than HICs and UMICs for both brand and generic medications. 20 In our previous publications from the PURE study, overall hypertension control was worst in LICs and LMICs (10.8%), with poor access to medicines among the reasons for the low frequency of treatment and control of hypertension in these countries.…”
Section: Discussionmentioning
confidence: 99%
“… 20 They also found that affordability was lower in LICs and LMICs than HICs and UMICs for both brand and generic medications. 20 In our previous publications from the PURE study, overall hypertension control was worst in LICs and LMICs (10.8%), with poor access to medicines among the reasons for the low frequency of treatment and control of hypertension in these countries. 6 21 The data in the majority of these studies are now dated, we need repeat assessments to track medication availability and affordability as these could change over time.…”
Section: Discussionmentioning
confidence: 99%